Extremal expansions of the non-negative operator and accretive boundary problems - Storozh, O. G. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
A method is proposed to describe the maximal nonnegative and the proper maximal accretive extensions of a nonnegative closed densely defined operator in a Hilbert space.